PENGUKURAN KUALITAS JASA - Maria Merry Marianti (Bina Ekonomi, 2009)
Service management is very important, because it determines Service Quality. Service Quality determines customer's satisfaction, and customer's satisfaction determines customer's behavior intentions. It is not easy to measure Service Quality, especially because service is intangible, but every service company which want to improve their service quality, should measure their service quality. We can measure service quality using SERVQUAL or SERVPERF. Research result determined that SERVPERF better than SERVQUAL.